The effect of wind run on transpiration and leaf temperature of Leucospermum concarpodendron on the Cape Peninsula - Karpul, Rebecca; Karpul, Rebecca (Department of Biological Sciences, 2017)
Parts of the Cape Floristic Region are subject to exceptionally elevated levels of wind in certain seasons, however it has recently been recorded that the Western Cape has experienced a reduction of 25.7% in wind run between the years 1974 - 2005. Shifts in wind run across the globe may significantly affect whole plant physiology through changes in transpiration which can inﬂuence mass-flow mediated movement of nutrients in winter as well as leaf temperature. The objectives of this study were to establish whether (a) decreased wind run could reduce transpiration in winter when vapour pressure deficit is low and (b)leaf temperature approaches damaging levels during low wind run conditions in Leucospermum conocarpodendron on the Cape Peninsula over a given time period. High levels of vapour pressure deficit (>l.5 kPa.w4hr⁻¹) did not occur simultaneously with high levels of wind run (>250 m.24hr⁻¹) and therefore the effects that these factors have on transpiration could be separated. Variable rates of transpiration corresponded with reduced wind run under low vapour pressure deficit conditions in winter, therefore decreased wind run may have the potential to reduce transpiration. However, transpiration is highly sensitive to minor ﬂuctuations in vapour pressure deficit during low wind run conditions. Variable leaf temperatures corresponded with low wind run and low vapour pressure deficit conditions, therefore decreased wind run may have the potential to increase leaf temperatures. However, leaf temperature is highly sensitive to low wind run and low vapour pressure deficit conditions. Low wind run conditions, currently predicted for the future, does not pose a threat to transpiration, nutrient uptake and leaf temperature of Leucospermum conocarpodendron plants on the Cape Peninsula.